Application of biomedical cell products in the treatment of congenital epidermolysis bullosa - Arfenya E. Karamova; Kseniya M. Aulova; Vadim V. Chikin; Аlexey A. Kubanov (Vestnik Dermatologii i Venerologii)
Congenital epidermolysis bullosa is a phenotypically and genetically heterogeneous group of genodermatoses, which are characterized by decreasing of skin’s structural protein production up to complete absence or violation of the structure as a result of mutation. Congenital epidermolysis bullosa clinically manifests by the development of blisters on the skin and mucous membranes after mechanical injury. The presence of long-term erosive and ulcerative defects in patients with congenital epidermolysis bullosa reduces the quality of patients’ life and also leads to malignancy of the lesions, as a result of constant stimulation of regenerative processes. Currently, in the treatment of patients with congenital epidermolysis bullosa symptomatic therapy, including prevention of secondary infections, use of pain medication and atraumatic non-adherent wound dressings and correction of complications, is widely used. Nevertheless there are a lot of publications describing the use of skin substitutes, three-dimensional tissue-engineered structures based on auto- and allogeneic cells that promote rapid epithelization of wounds in patients with congenital epidermolysis bullosa. Tissue-engineered skin substitutes can be categorised based on their cellular composition: epidermal substitutes consist of an epidermal layer of stratified keratinocyte sheets with or without an underlying acellular dermal layer containing scaffolding; dermal substitutes contain fibroblasts embedded within a scaffolded dermal matrix; composite substitutes are composed of an epidermal layer of stratified keratinocyte sheets and an underlying scaffolded dermal layer containing fibroblasts. The most prospective and at the same time the least studied direction of congenital epidermolysis bullosa treatment is the use of a combined skin equivalent created on the basis of keratinocytes and fibroblasts, which mixes the advantages of epidermal and dermal grafts.